Borderline personality disorder traits and mentalising ability: The self-other social cognition paradox - Kelly Grealy, Molly; Godfrey, Emmet; Brady, Finn; Whyte O’Sullivan, Erin; Carroll, Grace A.; Burke, Tom (Frontiers in Psychiatry, 2022)
Objective: Borderline personality disorder (BPD) is a psychiatric condition characterized by a pervasive pattern of impulsivity, low self-image, and interpersonal conflicts. Previous findings indicate a mixed relationship between BPD and social cognition; little research as investigated whether BPD traits influence performance on specific elements of social cognitive tasks i.e., positive/negative valence. Method: Community-based typical controls (n=151; 51% female) were recruited through an online survey. Participants completed aspects of the Personality Assessment Inventory pertaining to BPD traits, the Interpersonal Reactivity Index, and measures of both emotion recognition and mentalising. Results: Following group stratification into high/low BPD traits, participants with high BPD traits were observed to perform significantly better when identifying negative valence stimuli. Furthermore, high levels of affect instability was found to significantly influence negative valence recognition. Conclusion: This research highlights previous research which shows a paradox between higher performance on measures of social cognition, with a group of individuals who report significant interpersonal and relational difficulties. This research supports the assessment of social cognitive processes for people with BPD and/or high BPD traits to support clinical formulation of strengths and difficulties.